EQUITY OF THE ENTERPRISE: ECONOMIC ESSENCE AND FEATURES OF ACCOUNTING - Berzhanir I. А. (The actual problems of regional economy development, 2023)
The purpose of the article is the study of theoretical provisions and the development of practical recommendations for improving the accounting of the company's own capital. The following methods were used in the research process: methods of induction and deduction, the method of comparison, the method of generalization - to reveal and clarify the economic essence of equity capital and carry out its classification for the purpose of accounting; systematic approach - to build accounting support for managing one's own capital; statistical research methods - to assess the structure and dynamics of the company's equity capital; graphic - for a visual presentation of research results. The information base of the scientific research is the scientific works of domestic economists and normative acts on the organization of accounting of the company's own capital. The article examines the economic essence and structure of equity through the prism of national and international accounting standards. The composition and structure of the company's equity capital were diagnosed and the factors that influenced its change were analyzed. The theoretical and methodological foundations of the organization of equity accounting and its reflection in reporting in the context of national and international standards are considered. The scientific novelty of the results obtained is to determine and disclose the directions for improving the organization of accounting of equity in order to increase its turnover; application of automated systems for accounting of equity; use of a compromise approach to financing the assets of an entity; reduction of receivables that will accelerate capital turnover; Use of audit services for optimal accounting of reserves. The obtained research results can be used to create an effective equity accounting model, which will make it possible to avoid insolvency risks.